Energy plantations and irrigation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
By growing trees in irrigated areas one can contribute to both the energy self-sufficiency of such operations and their economic viability through the sale of surplus fuelwood or lumber. That is why the International Action Service of the French...